THE EXISTENCE OF UNIVERSAL VALUES OF ISLAMIC POLITICAL ETHICS IN THE FORMATION OF PUBLIC POLICY - Aulia, Astri; Afriani; Lestari, Tari; Kurniati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The formation of public policy is a fundamental aspect of modern government. In this context, the universal values of Islamic political ethics have a significant influence. Islamic political ethics rooted in the Qur'an and Hadith offer moral guidelines and principles that can be adopted in the public decision-making process. This research aims to explore how these values can influence public policy in different countries, especially the Muslim majority. This research uses a literature method with an Islamic law approach. The research will begin by conducting a comprehensive literature review of primary and secondary sources, including Islamic classics, scientific journals, books on Islamic political ethics, as well as public policy articles and reports. The results of the study show that universal values such as justice ('adl), benefit (maslahah), accountability (amanah), wisdom (hikmah), and public participation (shura) have significant relevance in the context of public policy formation. These values can help create policies that are more just, inclusive, and oriented towards community welfare. However, the application of these values is inseparable from various challenges, such as pluralistic contexts, diverse interpretations, and incompatibility with contemporary conditions